A strategy for extracting information from semi-structured web pages. - Shaker, Mahmoud; Ibrahim, Hamidah; Mustapha, Aida; Abdullah, Lili Nurliyana (2010)
Purpose – The aim of this paper is to propose a strategy for extracting information from web tables. Design/methodology/approach – The paper presents a strategy for extracting information from web tables of semi-structured web pages (WPs) by handling the issue of synonym which emerges as these WPs have been designed and created without referring to any standards or guidelines. Findings – The paper finds that this strategy extracts information with high precision, and extracts the attributes besides the sub-attributes that describe the extracted attributes and values of the sub-attributes. Practical implications – Experiment conducted on the Nokia products domain demonstrated that the proposed strategy extracts information from web tables with high precision which is 98.98 percent. Originality/value – This paper contributes to the research on extracting information.